Influenceh Humor Shows on Stress in Correctional Students - Arianingsih, Sri Endah (PELNUS | Pen en Light for Natural Union of Science, 2022)
The prison environment is an environment that limits people's freedom to act. People who are imprisoned lose their freedom. This causes more psychological suffering than corporal punishment and stresses the occupants. One technique that can be used to deal with stress is to use humor. Humor is the capacity to accept or express the amusing (funny) aspects of a situation and is manifested by laughing. Humor can produce positive emotions and is a means of releasing physical tension. Humor and laughter can quickly remove potential sources of pain and stress. This study took a sample of 29 students from Tanjung Gusta Penitentiary. Sampling was done by using random sampling. The measuring instrument used in this study is a stress scale which was compiled by the researcher based on the biological and psychological aspects of stress. This stress scale has a reliability value (rxx) = 0.903. The humor used is Mr. Bean's Holidays. The results of research data analysis using the Independent Sample Test show that humor shows have a significant influence on the stress of correctional students.